HUBUNGAN PERILAKU KONSUMTIF DAN WAKTU SENGGANG TERHADAP STATUS METROSEKSUAL PADA MAHASISWA FISIP UNIVERSITAS UDAYANA - Trisna Dewi, Ni Luh Kade; Zuryani, Nazrina; Agung Krisna Aditya, I Gusti Ngurah (JURNAL ILMIAH SOSIOLOGI (SOROT), 2020)
This study examines the positive relationship between consumptive behavior and leisure time on metrosexual status among students of the Faculty of Social and Political Sciences, Udayana University. Using the leisure class theory (Veblen, 1889), the consumptive behavior of students in the Faculty of Social and Political Sciences (FISIP) Udayana University was examined on the use of free time on metrosexual status. Data analysis used multiple linear regression techniques and classical assumption test. The results of the study using multiple correlation showed an interval range of 0.60 - 0.799 with a STRONG interval, which indicated a positive relationship between consumptive behavior and time shifting towards metrosexual status. The results of the classical assumption test, namely normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test show that this study has an error rate of 5%. Metrosexual status was explained by 57.4% from other observation factors. Keywords: Metrosexual, leisure class, consumptive behavior